2015
DOI: 10.1002/jso.23888
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of CCAT2 is associated with poor prognosis in esophageal squamous cell carcinoma

Abstract: Our study provides the first evidence associating CCAT2 expression and poor survival in ESCC. CCAT2 may be a prognostic biomarker and therapeutic target for ESCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 31 publications
5
74
0
Order By: Relevance
“…Many recent studies have shown that abnormal expression of lncRNA may be found in many types of cancer [11,13]. The formation and progress of esophageal cancer is a complicated, multistep, and progressive process that involves the regulatory effects of multiple genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent studies have shown that abnormal expression of lncRNA may be found in many types of cancer [11,13]. The formation and progress of esophageal cancer is a complicated, multistep, and progressive process that involves the regulatory effects of multiple genes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, H19 was the first lncRNA associated with cancer, which is upregulated in many types of human cancer, such as liver cancer, bladder cancer, and breast cancer, and functions as an oncogene [6,7]. Some tumor-related lncRNAs are also capable of serving as potential markers, and dysregulation of their expression is often related to the clinicopathological features and even prognosis of patients [8][9][10][11]. For example, MALAT-1 enhances the cell motility of lung adenocarcinoma and is treated as a specific marker of non-small cell lung cancer, especially in the early metastasis stage of lung adenocarcinoma [9].…”
mentioning
confidence: 99%
“…Multiple types of lncRNA have been identified as associated with the development and progression of ESCC, including pist, colon cancer-associated transcript 2, homeobox transcript antisense RNA and metastasis-associated lung adenocarcinoma transcript 1 (26)(27)(28)(29)(30)(31). SBF2-AS1 is a novel lncRNA transcribed on chromosome 11p15.1 and, previously, its function and molecular mechanism in NSCLC has been reported (14).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of linc-POU3F3 are increased in ESCC samples from patients compared with noncancerous tissues [ 104 ]. Elevated expression of lncRNA CCAT2 is associated with poor prognosis in esophageal squamous cell carcinoma [ 105 ].…”
Section: Lncrnas and The Esophagusmentioning
confidence: 99%